Strategi Pengembangan Usahatani Salak Pondoh (Salacca Edulis) di Kabupaten Rejang Lebong - Abu Sutikno; Febri Nur Pramudya; Dwita Prisdinawati (JINGLER : Jurnal Teknik Pengolahan Pertanian, 2025)
This research is to (1) Determine the internal factors (IFE) and external factors (EFE) of Pondoh salak farming in Rejang Lebong Regency. (2) Knowing the appropriate alternative strategy for developing pondoh salak farming in Rejang Lebong Regency. This research method was carried out qualitatively and quantitatively using a questionnaire. Location determination is carried out purposively on the farm shouted pondoh Mr. Andi in Air Merah Village, Curup Tengah District, Rejang Regency . The analysis used is IFE, EFE, SWOT MATRIX. The results of this research are the internal factors that are the main strengths of Mr. Andi's pondoh salak Sahatani are having their own land , competitive prices for salak , the availability of potential areas for developing salak . Weakness factors are the lack of understanding of snake fruit farmers regarding good snake fruit cultivation , limited capital , production is still low . External factors that become the biggest opportunities for Mr. Andi's pondoh salak farming business are the wide market share , quite large market demand , and fast return on investment . Threat factors are the increasingly limited land for salak farming , the presence of new competitors , the high prices of production facilities . Alternative strategies that can be utilized and applied in salak farming Mr. Andi 's cottage . The alternative obtained is an aggressive strategy that focuses more on the S - O (Strengths - Opportunities) strategy.